A fully sealed plastic chip for multiplex PCR and its application in bacteria identification1. Issue 13 (7th July 2015) - Xu, Youchun; Yan, He; Zhang, Yan; Jiang, Kewei; Lu, Ying; Ren, Yonghong; Wang, Hui; Wang, Shan; Xing, Wanli
<x xml:space="preserve">Abstract</x> A reversible centrifugation-based multiplex PCR chip is constructed and applied to identify 8 pathogenic bacteria and 13 drug-resistance genes.